PEMBERLAKUAN ASAS RETROAKTIF DALAM PEMBERANTASAN TINDAK PIDANA KORUPSI - I MADE ADI SERAYA (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2013)
The study entitled, "The implementation of the retroactive principle in fighting against corruption". The background of this research was derive from the fact that corruption is an extraordinary crime that needs an extra way against it. The formation of Corruption Eradication Commission (KPK) as an independent agency in the form of eradicating corruption in Indonesia has gradually demonstrated its role. But, Problems then occur when the citizen force KPK to handle the corruption cases before this constitution constructed, especially BLBI case which made this state inflict a financial loss about  Rp 138,4 trillions happen during  the 1997-1998. From the background it raised an issue, whether the retroactive principle can be applied by the Commission in the investigation, and prosecution of the perpetrators of corruption that occurred before the enactment of Law No. 30 Year 2002 was made on the Corruption Eradication Commission? In this discussion the retroactive principle can be applied by the Commission in making "a series of actions" which make it able to conduct an investigation and prosecution of the perpetrators of corruption despite they occurred before Law. 30 of 2002 on the Corruption Eradication Commission enacted. Besides confirming that the application of this principle is that corruption is a crime classified as an extraordinary crime which has wide negative effects to the country.